2019
DOI: 10.1176/appi.ps.201900007
|View full text |Cite
|
Sign up to set email alerts
|

Increases in Demand for Crisis and Other Suicide Prevention Services After a Celebrity Suicide

Abstract: This study examined data on acute (i.e., within 30 days) increases in suicides, help and information seeking, and service capacity after a celebrity suicide. Methods: Daily suicide data, call volume to the National Suicide Prevention Lifeline (NSPL), and visits to two suicide prevention Web sites before and after entertainer Robin Williams' death on August 11, 2014, were examined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 10 publications
0
9
1
Order By: Relevance
“…Indeed, those who are at heightened risk of suicide may reach a “tipping point” if their calls are unanswered. Ramchand et al (2019) commented on this when they reported their findings on increases in calls to major helplines in the United States, noting that the number of calls rose by up to 300% but that the average number of calls that could be answered decreased from 71% to 57%. In our study, we reported on the number of calls received for consistency because we had these data for both Lifeline and Beyond Blue.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Indeed, those who are at heightened risk of suicide may reach a “tipping point” if their calls are unanswered. Ramchand et al (2019) commented on this when they reported their findings on increases in calls to major helplines in the United States, noting that the number of calls rose by up to 300% but that the average number of calls that could be answered decreased from 71% to 57%. In our study, we reported on the number of calls received for consistency because we had these data for both Lifeline and Beyond Blue.…”
Section: Discussionmentioning
confidence: 99%
“…When the famous actor and comedian took his life by hanging on August 11, 2014, the US reporting was extensive and of variable quality, with a significant amount of coverage sensationalizing his suicide and describing the method he used in detail (Carmichael & Whitley, 2019). Fink, Santaella‐Tenorio, and Keyes (2018) showed that there were 10% more suicides in the United States in the subsequent five months that would have been expected on the basis of preexisting trends, and Ramchand et al (2019) reported similar findings over one month. This evidence suggests that the reporting of Williams’ death contributed to these excess suicides (Fink et al, 2018; Ramchand et al, 2019).…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…This less than optimal reporting was implicated in a 10% increase in US suicides in the 5 months after Williams' death observed by Fink et al (2018). Ramchand et al (2019) also suggested that the nature and quality of reporting may have influenced an equivalent increase that they observed in the United States over a shorter time frame (1 month).…”
Section: Introductionmentioning
confidence: 98%